Research Status and Prospects of Grouted Sleeve Connections in Prefabricated Structures - Qisheng Long; Mi Ding; Zhen Huang; Wenhao Ke; Zhaojian Hu (Buildings)
The application and promotion of grouted sleeve connectors in prefabricated structures are closely related to their high efficiency and intensive advantages. Numerous scholars have conducted experimental studies on the performance of sleeves, but there has been no systematic consolidation of these efforts. In this study, the latest developments in grouted sleeve connection technology are systematically reviewed and analysed, focusing on its applications and characteristics, performance testing, influencing factors, load-transfer mechanisms, and performance evaluation. First, the differences in sleeve code formulation across various countries are compared, the advantages and disadvantages of different sleeve types and grouting techniques are reviewed, and the application scenarios of sleeves are summarized. Second, an overview of the performance of grouted sleeves in tensile, fatigue, and seismic tests is provided, highlighting key factors affecting structural performance and experimental results. Furthermore, the effects of various factors (the anchorage length, diameter and strength of reinforcing bars; types and defects of grout materials; sleeve tube design; and temperature) on the performance of sleeves are investigated, and some beneficial conclusions are drawn. The load-transfer mechanisms of different sleeve types are subsequently compared, and the common features of the sleeves that meet the performance evaluation criteria are analysed. Finally, potential future research directions and innovations in sleeve technology are suggested to provide researchers and scholars with innovative ideas and research perspectives for developing new sleeves and advancing the application of grouted sleeve connectors.